PERFORMANCE OF SHARIA MUTUAL FUNDS IN INDONESIA - Sabila, Fadiyah Hani (Jurnal Ekonomi dan Bisnis Terapan, 2018)
This study aims to analyze the performance of sharia mutual funds in Indonesia, especially stock mutual funds with the 2015-2017 research period. The method was used by measuring the rate of return (rate of return) obtained and the risk (risk) that accompanies the investment. The data used in this study are secondary data with a sample of 15 sharia equity funds in Indonesia. To calculate the historical performance of mutual funds during the study period, the time-weighted rate of return and risk borne by the mutual funds method is calculated as the standard deviation of the mutual fund’s performance. The Sharpe method was used for comparison as well as rating the performance of mutual funds based on risk-adjusted return. The results showed that Cipta Syariah Equity Mutual Funds were Sharia Equity Funds that had the best performance compared with other Sharia Equity Funds